Gender difference in glyoxalase 1 activity of atherosclerotic carotid artery lesions - Peters, Andreas; Hakimi, Maani; Vittas, Spiros; Fleming, Thomas; Nawroth, Peter Paul; Böckler, Dittmar; Dihlmann, Susanne (Journal of vascular surgery, 2015)
Objective - Age and gender are two factors that determine the risk of atherosclerosis. The latter effect is only partly understood. Dicarbonyls, in particular methylglyoxal, participate in the development of atherosclerosis, and their major detoxification route is the enzyme glyoxalase 1 (GLO1), which is known to decrease during aging. - Methods - GLO1 expression and activity were studied in atherosclerotic carotid artery lesions of 71 patients with respect to demographic and clinical characteristics. - Results - GLO1 activity was nonsignificantly reduced by >50% in individuals with carotid artery disease compared with control individuals. There was no significant difference in GLO1 expression between the groups; however, the GLO1 activity-to-protein ratio showed a significant reduction for the carotid artery disease patients compared with the controls. The reduction in the GLO1 activity-to-protein ratio was more pronounced in men and was associated with increased inflammation shown by a significant elevation in the expression-level of interleukin-1β. - Conclusions - These data suggest that GLO1 is regulated on the post-translational level by factors such as gender as well as factors that affect the overall burden of atherosclerosis.